MECHANISMS FOR REGULATING ECOLOGICAL PROBLEMS IN AGRIBUSINESS(THE CASE OF GEORGIA) - KADAGISHVILI, LEILA; BEZHITASHVILI, NATALIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Natural resources are a national treasure which forms the material basis for the development of the country. Rational and complex use of these resources determines economic self-sufficiency of the country and raising the economic well-being of its population. A significant part of the progressive-minded people around the world agree that due to the impact of economic activities on the environment, the excessive and often irrational use of natural resources in the contemporary world, the present society faces with numerous local and global problems in terms of environmental pollution, which have become even more acute in recent years. Disturbance of the natural balance of the environment is closely connected to the intensification of agricultural activities. No other field of economic activity is so much related to the use of natural resources as agriculture. With the purpose to meet the needs of the society, agribusiness uses the resources that are available in nature and impacts the environment that results in a wider degradation of the latter. The scarcity of land, water and other types of resources is becoming more and more evident. The importance of normalization of the relationship between agribusiness and environment for maintaining ecological balance of the environment is increasing and this implies not the reduction of such activities, but a careful and saving attitude towards the environment. The protection of the environment and the rational use of natural resources along with the development of agriculture is an essential precondition for the sustainable development of our country. The present paper does not aim to fully assess the environmental problems caused by agribusiness. The paper assesses three important environmental problems - soil degradation, threats due to plant and animal waste, and threats from mineral fertilizers and chemicals. In addition, mechanisms for regulating these problems are provided.